Rare coding variants in genes encoding GABAA receptors in genetic generalised epilepsies: an exome-based case-control study. Issue 8 (August 2018) - May, Patrick; Girard, Simon; Harrer, Merle; Bobbili, Dheeraj R; Schubert, Julian; Wolking, Stefan; Becker, Felicitas; Lachance-Touchette, Pamela; Meloche, Caroline; Gravel, Micheline; Niturad, Cristina E; Knaus, Julia; et al.
Summary: Background: Genetic generalised epilepsy is the most common type of inherited epilepsy. Despite a high concordance rate of 80% in monozygotic twins, the genetic background is still poorly understood. We aimed to investigate the burden of rare genetic variants in genetic generalised epilepsy. Methods: For this exome-based case-control study, we used three different genetic generalised epilepsy case cohorts and three independent control cohorts, all of European descent. Cases included in the study were clinically evaluated for genetic generalised epilepsy. Whole-exome sequencing was done for the discovery case cohort, a validation case cohort, and two independent control cohorts. The replication case cohort underwent targeted next-generation sequencing of the 19 known genes encoding subunits of GABAA receptors and was compared to the respective GABAA receptor variants of a third independent control cohort. Functional investigations were done with automated two-microelectrode voltage clamping in Xenopus laevis oocytes. Findings: Statistical comparison of 152 familial index cases with genetic generalised epilepsy in the discovery cohort to 549 ethnically matched controls suggested an enrichment of rare missense (Nonsyn) variants in the ensemble of 19 genes encoding GABAA receptors in cases (odds ratio [OR] 2·40 [95% CI 1·41–4·10]; pNonsyn =0·0014, adjusted pNonsyn =0·019). Enrichment for these genes was validated in a whole-exome sequencing cohort of 357 sporadic and familial genetic generalised epilepsy cases and 1485 independent controls (OR 1·46 [95% CI 1·05–2·03]; pNonsyn =0·0081, adjusted pNonsyn =0·016). Comparison of genes encoding GABAA receptors in the independent replication cohort of 583 familial and sporadic genetic generalised epilepsy index cases, based on candidate-gene panel sequencing, with a third independent control cohort of 635 controls confirmed the overall enrichment of rare missense variants for 15 GABAA receptor genes in cases compared with controls (OR 1·46 [95% CI 1·02–2·08]; pNonsyn =0·013, adjusted pNonsyn =0·027). Functional studies for two selected genes ( GABRB2 and GABRA5 ) showed significant loss-of-function effects with reduced current amplitudes in four of seven tested variants compared with wild-type receptors. Interpretation: Functionally relevant variants in genes encoding GABAA receptor subunits constitute a significant risk factor for genetic generalised epilepsy. Examination of the role of specific gene groups and pathways can disentangle the complex genetic architecture of genetic generalised epilepsy. Funding: EuroEPINOMICS (European Science Foundation through national funding organisations), Epicure and EpiPGX (Sixth Framework Programme and Seventh Framework Programme of the European Commission), Research Unit FOR2715 (German Research Foundation and Luxembourg National Research Fund).